Distribution of endangered and protected species of synanthropic plants in Łask - Suwara-Szmigielska, Sylwia (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2008)
The article presents description and distribution of protected and endangered species of synanthropic plants found in the Łask area in 2001-2002. The research was carried out with the use of a cartogram method. As a result, ten species of protected plants were found in the researched area, four of which under strict protection, and six under partial protection. Eight out of the ten protected species are in the danger of extinction.